Motivasi Guru Pendidikan Jasmani Dalam Melaksanakan Pembelajaran Jarak Jauh Di Sekolah Menengah Atas Se-Kecamatan Cikarang Utara Saat Pandemi Covid-19 - Adam Wijaya; Setio Nugroho; Rizki Aminudin (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine how high the level of motivation of physical education teachers in implementing distance learning in high schools throughout North Cikarang District is during the covid-19 pandemic. This research is a quantitative descriptive. The method used in this study is a survey method, data collection techniques using a questionnaire in the form of a Likert scale. The subjects in this study were physical education teachers in high schools throughout the North Cikarang sub-district, totaling 14 teachers. The data analysis technique used quantitative descriptive analysis as outlined in percentages. The results of this study indicate that the level of motivation of physical education teachers in implementing distance learning is in the categories of "very low" 7%, "low" 14%, "enough" 50%, "good" 21%, and "very good" 7% .